Span of Control in Teamwork and Organization Structure - Katarina Remenova; Zuzana Skorkova; Nadezda Jankelova (Montenegrin Journal of Economics)
The span of control expresses how many subordinates correspond to one manager, while determined by many factors and unable to be expanded indefinitely. The study monitors the impact of determinants, like the functional area of control, the level of management, the duration of managerial position, the age of the manager, the size and composition of the team. The results of non-parametric testing (Chi-Square Test of Independence) and rates of association between variables (using Cramér’s V and Phi coefficient and for ordinal variables, Kendall’s tau-b, GoodmanKruskal’s Gamma, Kendall’s tau-c and Somers’ d) indicate that the team size is not related to the level of management, which does not confirm the assumption that the largest teams work at the lowest management level and vice versa, that the team leader at the top level is in charge of the smallest number of people. Instead the size of the team depends on the functional area of control. The assumption that increasing age, and so increasing experience also increases the size of the team, has not been confirmed. However, the fact that the manager works longer in the leading position has been confirmed. With the current manner of managing an organization, the age of the manager is the weak indicator of the duration of the managerial position.